Creative economy development strategy in eco-print industry: SOAR Analysis and Sharia Perspective - Hapsari, Mega Tunjung; Adibah, Ayuk Wahdanfiari (al-Uqud : Journal of Islamic Economics, 2023)
This research aims to develop a creative economy eco-print in Kediri Residency through SOAR analysis and sharia perspectives. This study used qualitative methods. Primary data was obtained from interviews with eco-printers, and secondary data from documents and internet sources. The analysis technique uses an interactive model that describes the overall field research process. The results of the SOAR analysis in the study show that the strength of the eco-print industry in Kediri Residency lies in the availability of raw materials, product quality, and relatively affordable prices. In terms of opportunities, it can open employment opportunities and potential markets from within and outside the country. The aspirations indicate the need for product development from professional institutions and collaboration. The research results are business development, increased sales, and eco-friendly lifestyle trends. In the analysis of the Sharia perspective, it can be concluded that the eco-print business has implemented the principles of Tauhid (rest at prayer times), 'adl (wages according to working hours, bonuses according to sales), Khilafah (basic principles of Islamic financial accounting), Nubuwwah (wisdom, responsibility, communication, and marketing), and Ma'ad (quality of raw materials and product innovation). This research implies that using Islamic values in business can help SMEs increase their productivity, which will ultimately positively impact SME performance and the development of the creative economy.